Workplace Bullying among Business Professionals: Prevalence, Gender Differences and the Role of Organizational Politics - Denise Salin (Perspectives Interdisciplinaires sur le Travail et la Santé)
The aim of this article is to describe the prevalence of bullying experienced by business professionals and to further the understanding of bullying by analyzing to what extent gender aspects and organizational politics may contribute to bullying in knowledge-intensive career-oriented jobs. The study was conducted as a cross-sectional survey study among members of a professional organization for employees with a university degree in business studies. In addition, written stories were collected to increase the understanding of bullying. This article presents data on the prevalence of bullying, gender differences in bullying, and the relationship between bullying and organizational politics. In addition, some implications for both researchers and managers are presented. The article is based on the author’s doctoral thesis.